Stimulasi Kecerdasan Interpersonal melalui Penerapan Model Sentra di TK Penyemai Bungursari - Jihan Fauziah; Suci Utami Putri; Tiara Lintang Utami (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to explore the implementation of the center-based learning model in stimulating interpersonal intelligence among early childhood learners at TK Penyemai Bungursari. The research focuses on supporting factors, required resources, and challenges encountered in implementing the center-based model. Using a qualitative approach with a case study method, the study involved 21 children from Groups A and B, teachers, and the school principal as participants. Data were collected through observation, semi-structured interviews, and documentation. The findings indicate that the stimulation of interpersonal intelligence was carried out through the Small Circle Big Impact (SCBI) approach, which emphasizes intensive interaction within small groups. Key supporting factors included Circle Time activities, the arrangement of a democratic play environment, and the reinforcement of positive communication through the use of magical words. Despite challenges related to limited facilities and infrastructure, the model proved effective in enhancing children’s cooperation, empathy, and communication skills.